Adults with intellectual disabilities and/or autism who deliberately set fires: A systematic review. (January 2021) - Collins, J.; Barnoux, M.; Langdon, P.E.
Abstract: Fire setting behaviour has devastating consequences and a significant number of adults who set fires have intellectual disabilities and/or autism. However, there has been no comprehensive review of the characteristics and treatment needs of this group of offenders, with existing reviews being limited in terms of sample population and methodological rigour. The purpose of this review was to systematically examine and synthesise existing research to determine what is known about adults with intellectual disabilities and autism who set fires. PsychINFO, PsychARTICLES, Medline, CINAHL Plus with Full Text, Criminal Justice Abstracts, SCOPUS, Open Grey, and the University of Kent arson library were searched for articles. The methodological quality of studies was assessed using the Mixed Methods Appraisal Tool. Searches resulted in 100 articles that met the specific inclusion criteria. Findings indicated adults with intellectual disabilities and autism share some characteristics with other adults who set fires (e.g. aggression, impulsivity). They also face additional challenges, which may have implications for treatment and risk formulation (e.g. communication difficulties, lack of support). However, current research is generally of poor methodological quality, limiting our ability to understand the unique characteristics and treatment needs of this population. Highlights: Adults with intellectual disabilities and autism set fires. This remains rare. They share some of the same characteristics as other adults who set fires. There is evidence to suggest they have unique characteristics. The research that has been conducted is of poor methodological quality. More research is needed to improve our understanding of all adults who set fires.